2017
DOI: 10.1089/rej.2016.1823
|View full text |Cite
|
Sign up to set email alerts
|

The Clinical Efficacy of Autologous Platelet-Rich Plasma Combined with Ultra-Pulsed Fractional CO2 Laser Therapy for Facial Rejuvenation

Abstract: Ultra-pulsed fractional CO2 laser is an efficient, precise, and safe therapeutic intervention for skin refreshing, although accompanied with prolonged edema and erythema. In recent years, autologous platelet-rich plasma (PRP) has been proven to promote wound and soft tissue healing and collagen regeneration. To investigate whether the combination of PRP and ultra-pulsed fractional CO2 laser had a synergistic effect on therapy for facial rejuvenation. Totally, 13 facial aging females were treated with ultra-pul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
4
10

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(55 citation statements)
references
References 32 publications
2
35
4
10
Order By: Relevance
“…Also to assess the synergistic effect of PRP and ultra‐pulsed fractional CO2 laser, another RCT study was performed among 13 facial aging females. After a 3‐month treatment, experimental group showed excellent improvement of skin wrinkles and the total duration of erythema and edema, while crusting was decreased, compared to the control group …”
Section: Application Of Prpmentioning
confidence: 98%
“…Also to assess the synergistic effect of PRP and ultra‐pulsed fractional CO2 laser, another RCT study was performed among 13 facial aging females. After a 3‐month treatment, experimental group showed excellent improvement of skin wrinkles and the total duration of erythema and edema, while crusting was decreased, compared to the control group …”
Section: Application Of Prpmentioning
confidence: 98%
“…PRFM not only contains various growth factors, but also produces no adverse effects, such as immune rejection. It does not have limitations in terms of economic accessibility, even for extensive corrections, and can be used effectively both for the soft tissue augmentation of facial deficits and for general filler applications, such as wrinkle correction [17,18]. Therefore, since PRFM is effective at restoring deficits, and the growth factors also stimulate regeneration by inducing proliferation of the surrounding skin, PRFM could enhance skin elasticity and correct shallow wrinkles.…”
Section: Discussionmentioning
confidence: 99%
“…PRFM filler from autologous plasma is made up of the patient's own blood, which means that it produces no immune rejection. It has few economic limitations for extensive correction, contains various growth factors that enhance skin regeneration, and is effective at improving skin elasticity and correcting wrinkles [3,[14][15][16][17][18].…”
Section: Discussionmentioning
confidence: 99%
“…They observed that from the second application, there was an improvement of fine wrinkles and skin tone; and at the end of the sessions, it was observed that most of the wrinkles had disappeared and there was facial restoration (Ulusal, ). Moreover, it was shown that the combination of PRP and ultra‐pulsed fractional CO 2 laser shortened the duration of laser side effects and improved the efficacy of the treatment after 3 months (Hui, Chang, Guo, Zhang, & Tao, ).…”
Section: The Prp In Dermatologymentioning
confidence: 99%